The Influence of International Law on the Enforcement of State Sovereignty Over Digital Resources - Rakhmi, Wendy Budiati (LEGAL BRIEF, 2024)
This research examines the influence of international law on the enforcement of state sovereignty over digital resources, focusing on a comparison of digital sovereignty policies in the European Union, the United States and China. With the rapid development of technology and the increasing reliance on digital infrastructure, many countries have sought to strengthen their digital sovereignty to protect data, privacy and national security. However, the absence of comprehensive international legal instruments poses challenges in the fair and uniform enforcement of digital sovereignty. This research uses a qualitative-descriptive approach with a multiple case study method, analyzing legal documents, national policies, and reports of relevant international organizations to identify the impact of international law on digital regulation. The results show that the European Union places privacy rights as a priority by implementing the General Data Protection Regu-lation (GDPR), while the United States tends to support market freedom and technological innovation, but with some exceptions related to national security. China, on the other hand, takes a protectionist and centralized approach with strict control over data and digital access in its territory. In conclusion, these different approaches result in fragmentation in the management of digital sovereignty, which could threaten global connectedness. This research recommends international cooperation to create a global digital legal framework that balances state sovereignty rights with the need for connectedness and equitable access to data around the world